2009
DOI: 10.1534/genetics.109.101105
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Analysis Reveals Novel Pathways Affecting Endoplasmic Reticulum Homeostasis, Protein Modification and Quality Control

Abstract: To gain new mechanistic insight into ER homeostasis and the biogenesis of secretory proteins, we screened a genomewide collection of yeast mutants for defective intracellular retention of the ER chaperone, Kar2p. We identified 87 Kar2p-secreting strains, including a number of known components in secretory protein modification and sorting. Further characterization of the 73 nonessential Kar2p retention mutants revealed roles for a number of novel gene products in protein glycosylation, GPIanchor attachment, ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 58 publications
3
46
0
Order By: Relevance
“…the intra-ER chaperone Kar2 (a BiP homolog). The slow leak of Kar2 from the ER, through the Golgi and its secretion into the medium is a good way to observe dysregulated secretion (Copic et al, 2009). Indeed, overexpressing GFP-Pex35 (which led to a drastic increase in Arf1 levels) decreased secretion to 50% or less, similar to what is seen upon directly overexpressing Arf1 (Fig.…”
Section: Pex35 Modulates the Effect Of Arf1supporting
confidence: 54%
“…the intra-ER chaperone Kar2 (a BiP homolog). The slow leak of Kar2 from the ER, through the Golgi and its secretion into the medium is a good way to observe dysregulated secretion (Copic et al, 2009). Indeed, overexpressing GFP-Pex35 (which led to a drastic increase in Arf1 levels) decreased secretion to 50% or less, similar to what is seen upon directly overexpressing Arf1 (Fig.…”
Section: Pex35 Modulates the Effect Of Arf1supporting
confidence: 54%
“…Thus, cwc21D causes reduced levels of Erd2p and the additional loss of Erd1p may explain the growth defect. In support of this, another genome-wide screen showed that Cwc21p has a significant role in ER homeostasis; deletion of CWC21 causes unregulated ER to Golgi transport (Copic et al 2009). …”
Section: Cwc21 Interacts Genetically With Isy1mentioning
confidence: 94%
“…Expression of SRm300/SRRM2 also increases by 2.6-fold upon induction by calcium (Zagranichnaya et al 2005), suggesting a conserved mode of regulation. The link between Cwc21p, ERD2 pre-mRNA splicing, and ER homeostasis (Copic et al 2009) discussed above may be relevant to this.…”
Section: Cwc21p In the Regulation Of Splicingmentioning
confidence: 97%
“…However, htz1D mutants have pleiotropic phenotypes: they grow poorly and are temperature sensitive , have membrane and ER defects (Lockshon et al 2007;Copic et al 2009), and show synthetic sickness/lethality with a very wide range of other chromatin-related mutants (Collins et al 2007). Two recent studies have cast doubts on whether the effects observed in htz1D mutants in S. cerevisiae are caused by loss of H2A.Z or by the "frustrated" activity of the Swr1 complex in the absence of H2A.Z (Halley et al 2010;Morillo-Huesca et al 2010a).…”
Section: Roles For H2az In Transcriptionmentioning
confidence: 99%